RENJANA WEDARI, INNOVATIVE GARDENS AS PUBLIC HEALING SPACE - Islami, Rizky Citra; Rr. Tiara Intan Pertiwi; Muhammad Kharisma Bimantoro; Anis Sulistianingsih (International Journal on Livable Space, 2025)
Mental health has become a familiar topic for public discussion. One of the factors in the disruption of a person's mental health is the pressures and responsibilities from the environment. Indonesia is reported by UNICEF as one of 21 countries that has a large number of depressions. Social pressure in Indonesia is also one of the causes of mental disorders. Semarang as an industrial city had a large number of factories. Most factories implement a labor-intensive system that allows for high levels of worker fatigue. The idea of a public healing space is an innovative solution that can cure burnout. Research has shown that nature can reduce stress levels and anxiety. Nature is also a solution to improve mood, and increase stamina. Aims: The aim of this study is to  Renjana Wedari is an innovation park built as a public healing space for recreation, education, and public interaction. Methodology and results: The research method is qualitative by collecting data through field observations. The data input is used to make site planning as site analysis and determine the site development. Architectural design produces a concept based on site analysis from solar orientation, wind orientation, noise, view, and circulation. The site analysis is overlaid by its orientation, which determines the site development. The results of the site development are used to define the building form, material selection, vegetation concepts, and public activity needs. The research result is designed to build a public healing space for factory workers in Semarang. Conclusion, significance and impact study: The result showed that the design can fulfill the livable space in Semarang. There are several concerns for this design such as, connection with nature, open space for physical activity, design that supports tranquility, separate zones for privacy, inclusive approach, and environmental education.